Healthy Hearts, Healthy Lifestyles Club: an after-school intervention to promote cardiovascular health in elementary students - Jensen, Brittni Anne, author; Nelson, Tracy, advisor; Browning, Ray C., committee member; Cunningham-Sabo, Leslie, committee member (Colorado State University. Libraries, 2013)
Obesity and its comorbidities play an immense role in the development of cardiovascular disease (CVD). With its reputation as the number one cause of death in the United States, prevention and attenuation of risk factors for cardiovascular disease is of vital importance. Risk factors have been found in children as young as 6 years old, eliciting public health interventions aimed at addressing these risk factors before they develop into adulthood disease. PURPOSE: We developed an after-school pilot intervention program entitled Healthy Hearts, Healthy Lifestyles Club at Lopez Elementary School in Fort Collins, Colorado. The goal of this initiative was to educate 4th and 5th grade students on heart healthy lifestyles, including physical activity, dietary behaviors, and stress awareness. We also sought to encourage the students to "educate" their families about these behaviors. METHODS: We utilized information gathered from parent and student focus groups to design and implement an after-school program once a week for five weeks for 5th grade students and again for eight weeks for both 4th and 5th grade students. The curriculum consisted of various physical activity games, healthy snack preparation, and lessons on heart health and building leadership qualities to foster heart health knowledge, a necessary precursor to transformation in behavior. Changes in heart health knowledge and behaviors were analyzed through self-reported pre and post-tests given to students and their parents/guardians. RESULTS: A total of 11 students participated in Part I of the program, (Pre-test: n=11 fifth grade students, n=9 parents/guardians; Post-test: n=9 fifth students, n=4 parents/guardians), and 17 students participated in Part II of the program, (Pre-test: n=7 fourth grade students, n=5 fifth grade students, n=10 parents/guardians; Post-test: n=7 fourth grade students, n=6 fifth grade students, n=4 parents/guardians). Students and their parents/guardians showed improvement on several health knowledge and behavior parameters, namely increased recognition of unsaturated fat as a healthier option, (Part I: 33.3% to 44.4% students; Part II: 40% to 60% fourth grade students, 0% to 25% fifth grade students), and enhanced ability to provide examples of saturated and unsaturated fats, (Part I: 50% to 75% parents/guardians; Part II: 66.7% to 100% parents/guardians). Additionally, more participants reported zero days of high fat food consumption, (Part I: 11.1% to 33.3% students, 25% to 50% parents/guardians), more reported eating 5 servings of fruits and vegetables every day (Part I: 50% to 75% parents/guardians; Part II: 80% to 100% fourth grade students, 33.3% to 100% parents/guardians), and performing exercise on additional days of the week (Part II: 60% to 80% fourth grade students). CONCLUSIONS: Multi-component after-school programs may be viable channels through which CVD risk factors can be targeted in youth. Tailoring heart health knowledge to promote healthy behaviors in students may elicit improved knowledge and behaviors within the family.
Keywords: after-school; intervention; Healthy Hearts Club; elementary students; cardiovascular